A Bovine PeptideAtlas of milk and mammary gland proteomes - Bislev, Stine L. (Proteomics, 2012)
Proteome information resources of farm animals are lagging behind those of the classical model organisms despite their important biological and economic relevance. Here we present a Bovine PeptideAtlas, representing a first collection of bovine proteomics datasets within the PeptideAtlas framework. This database was built primarily as a source of information for designing selected reaction monitoring assays for studying milk production and mammary gland health, but it has an intrinsic general value for the farm animal research community. The Bovine PeptideAtlas comprises 1921 proteins at 1.2% false discovery rate (FDR) and 8559 distinct peptides at 0.29% FDR identified in 107 samples from 6 tissues. The PeptideAtlas web interface has a rich set of visualization and data exploration tools, enabling users to interactively mine information about individual proteins and peptides, their genome mappings, and supporting spectral evidence.